¿Promesas idealistas? América Latina en tiempos de la Responsabilidad de Proteger. - Serrano Carreto, Mónica del Carmen (El Colegio de México A.C., 2017)
This article explores why Latin American countries have endorsed, or objected to, the principle of the responsibility to protect (R2P). Over the past decades Latin American leaders have weighed the relative merits of the principle against the risk of intervention to prevent or respond to atrocity crimes. The article investigates some of the factors that have shaped Latin American leaders´ decisions vis-à-vis R2P. Through an exploration of the various positions held by Latin American countries in international discussions on R2P I aim to account for the role that the region has played in international efforts to develop and consolidate the R2P norm. Drawing on the countries’ recent history we find that those countries that experienced mass atrocities have been more willing to accept the R2P. As the analysis suggests, assessments of the relative costs and benefits of a multilateral solution to atrocity crimes have been influenced by the countries’ own record of massive human rights violation and democratization process. While the article argues that the sympathy shown by many Latin American countries to this principle was deeply rooted in the evolution and practice of human rights norms within the region, it situates current R2P discourse and practice in a context of regional contestation over human rights and rampant criminal homicidal violence. It concludes that in such a context the capacity of Latin American countries to engage normatively with R2P will most likely wane.